1997
DOI: 10.2527/1997.75123307x
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of amino acids from the intestine and their net flux across the mesenteric- and portal-drained viscera of lambs.

Abstract: Experiments were conducted to compare the rates of apparent absorption (disappearance) of individual essential amino acids (EAA) from the small intestine with their net fluxes across the mesenteric- (MDV) and portal- (PDV) drained viscera in sheep given a pelleted alfalfa diet at two levels of intake. Disappearances of individual EAA across the region of the small intestine drained by the mesenteric arcade (jejunum to ileum) were similar to those across the whole of the small intestine (duodenum to ileum). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
48
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 23 publications
12
48
2
Order By: Relevance
“…This suggests an increase in AA disappearance from the small intestine of the infected lambs, although the apparent absorption from the small intestine and net flux of AA across the MDV were similar between treatments. The net flux of AA across the MDV in the current study (1 to 5 g/day) is similar to the 4 to 6 g/day reported by MacRae et al (1997b) at similar intakes, but the similar net fluxes of AA across the MDV between control and parasitised lambs contrast with the observations for leucine by Yu et al (2000). While mesenteric plasma flows are within the ranges in the literature for sheep at a similar age and DM intake (700 to 1000 ml/min; Janes et al, 1985;MacRae et al, 1997b;Yu et al, 2000;Bermingham et al, 2007b), they are highly variable (CV of 28% to 40% in the control and parasitised lambs, respectively), and this variability may have masked any effects of infection on MDV AA fluxes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This suggests an increase in AA disappearance from the small intestine of the infected lambs, although the apparent absorption from the small intestine and net flux of AA across the MDV were similar between treatments. The net flux of AA across the MDV in the current study (1 to 5 g/day) is similar to the 4 to 6 g/day reported by MacRae et al (1997b) at similar intakes, but the similar net fluxes of AA across the MDV between control and parasitised lambs contrast with the observations for leucine by Yu et al (2000). While mesenteric plasma flows are within the ranges in the literature for sheep at a similar age and DM intake (700 to 1000 ml/min; Janes et al, 1985;MacRae et al, 1997b;Yu et al, 2000;Bermingham et al, 2007b), they are highly variable (CV of 28% to 40% in the control and parasitised lambs, respectively), and this variability may have masked any effects of infection on MDV AA fluxes.…”
Section: Discussionsupporting
confidence: 89%
“…The net flux of AA across the MDV in the current study (1 to 5 g/day) is similar to the 4 to 6 g/day reported by MacRae et al (1997b) at similar intakes, but the similar net fluxes of AA across the MDV between control and parasitised lambs contrast with the observations for leucine by Yu et al (2000). While mesenteric plasma flows are within the ranges in the literature for sheep at a similar age and DM intake (700 to 1000 ml/min; Janes et al, 1985;MacRae et al, 1997b;Yu et al, 2000;Bermingham et al, 2007b), they are highly variable (CV of 28% to 40% in the control and parasitised lambs, respectively), and this variability may have masked any effects of infection on MDV AA fluxes. High variability (.25%) in blood flow across the MDV has been observed previously (MacRae et al, 1997b;Yu et al, 2000), and might be attributed to either incomplete mixing of the dye in those blood vessels or movement of the catheter due to peristaltic intestinal contractions (MacRae et al, 1997b).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, abomasal infusion will probably reduce the AA available for milk production compared with intravenous infusions. It has been shown that there is a high rate of energy and protein turnover in the lumen wall and the PDV (Cant et al, 1996;Reynolds, 2002) and that there is a substantial metabolism of EAA during absorption by intestinal enterocytes (MacRae et al, 1997). Elevated luminal nutrient supply has shown to influence activity which promotes tissue growth (Cant et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…These measurements represent the net supply of AA after metabolism by the PDV during absorption and from arterial blood. As the PDV is a heterogonous collection of tissues, including the small intestine, reticulorumen, hindgut, pancreas, muscle and other tissues that do not have access to the AA during their absorption, measurement of net mesenteric-drained viscera (MDV; the tissues drained by the cranial mesenteric vein) release of AA provides a closer approximation of the true supply of AA from the small intestine, especially for sheep (MacRae et al, 1997b;Ré mond et al, 2003). In sheep, the net PDV release of EAA represented about 65% of the net release across the MDV, reflecting the uptake of EAA from arterial blood by the reticulorumen and other tissues not drained by the cranial mesenteric vein.…”
Section: Factors Affecting the Efficiency Of N Utilization In The Pdvmentioning
confidence: 99%